PENERAPAN MEDIA AUDIOVISUAL DALAM PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA BANJAR PADA SISWA KELAS V SDN 3 KAPAR KABUPATEN TABALONG PROVINSI KALIMANTAN SELATAN - Hidayatullah, Muhammad Syarif; Yulieda Hermaniar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of audiovisual media in teaching Banjar language speaking skills to fifth-grade students at SDN 3 Kapar, the students' responses to the use of such media, and the challenges teachers face in applying audiovisual media to Banjar language instruction. It is a qualitative study employing a descriptive approach, utilizing observation, interviews, and documentation for data collection. Data analysis involved the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the use of audiovisual media supported the learning process for the fifth-grade students at SDN 3 Kapar. Students responded positively to the audiovisual media, as the lessons became more engaging and easier to comprehend, while also boosting student participation and confidence in speaking the Banjar language. Nine students achieved a score of 5 (excellent), and four students achieved a score of 4 (good). Challenges encountered during implementation included limited supporting facilities, varying levels of student proficiency in the Banjar language, and the use of languages ​​other than Banjar in the students' environment.